PENGUJIAN SIFAT FISIK GABRO DAN SERPENTINIT DI SAOKA KOTA SORONG PROVINSI PAPUA BARAT - Abraham Sengka; Karmila Laitupa (INTAN Jurnal Penelitian Tambang, 2022)
Sorong City, especially in the Saoka area, has a hypothetical gabbro resource of 25,000,000 m3, and in the Rufei area it has a hypothetical serpentinite resource of 500,000 m3. but there is no test on the physical properties of the two rocks, so it is necessary to test the physical properties of gabbro and serpentine to determine the parameters of physical properties such as bulk density, specific gravity, water content, porosity, void ratio, and degree of saturation. The research method used is quantitative by taking samples at the research location and then conducting tests in the laboratory, the test results show the average physical properties of gabbro, namely original bulk weight = 3.09 gr/cm3, dry bulk weight = 3.01 gr/ cm3, saturated weight = 3.13 g/cm3, apperent specific gravity = 3.01, true specific gravity = 3.41, original water content = 2.55%, saturated water content = 3.91%, degree of saturation = 66.15%, porosity = 11.78%, void ratio = 0.13. Meanwhile, serpentinite has an average density of original = 2.57 gr/cm3, dry weight = 2.55 gr/cm3, saturated weight = 2.59 gr/cm3, apperent specific gravity = 2.55, true specific gravity = 2.67, original water content = 0.9%, saturated water content = 1.76%, degree of saturation = 48.19%, porosity = 4.46%, void ratio = 0.04.